Food Insecurity Is Associated With Inflammation Among Women Living With HIV. (27th August 2018) - Leddy, Anna M; Roque, Annelys; Sheira, Lila A; Frongillo, Edward A; Landay, Alan L; Adedimeji, Adebola A; Wilson, Tracey E; Merenstein, Daniel; Wentz, Eryka; Adimora, Adaora A; Ofotokun, Igho; Metsch, Lisa R; et al.
Abstract: Background: Chronic inflammation is associated with AIDS-defining and non-AIDS–defining conditions. Limited research has considered how food insecurity influences chronic inflammation among people living with human immunodeficiency virus (HIV). We examined whether food insecurity was associated with higher levels of inflammation among women living with HIV (WWH) in the United States. Methods: We analyzed cross-sectional data collected in 2015 from 421 participants on antiretroviral therapy from the Women's Interagency HIV Study. The exposure was any food insecurity. The outcome was inflammation, measured by proinflammatory cytokine interleukin-6 (IL-6) and tumor necroses factor receptor 1 (TNFR1) levels. We conducted multivariable linear regressions, adjusting for sociodemographic, clinical, and nutritional factors. Results: Nearly one-third of participants (31%) were food insecure and 79% were virally suppressed (<20 copies/mL). In adjusted analyses, food insecurity was associated with 1.23 times the level of IL-6 (95% confidence interval [CI], 1.06–1.44) and 1.13 times the level of TNFR1 (95% CI, 1.05–1.21). Findings did not differ by HIV control (virally suppressed with CD4 counts ≥500 cells/mm 3 or not) in adjusted stratified analyses. Conclusion: Food insecurity was associated with elevated inflammation among WWH regardless of HIV control. Findings support the need for programs that address food insecurity among WWH. Abstract : Among a sample of women living with HIV in the United States, food insecurity was associated with elevated levels of proinflammatory cytokines interleukin-6 and tumor necrosis factor receptor 1, regardless of HIV control.